ANALISIS KEBUTUHAN TENAGA KERJA KESEHATAN BERDASARKAN BEBAN KERJA DENGAN METODE WISN DI PUSKEMAS PEMATANG JAYA - Sari, Winda Permata; Ginting, Daniel; Dachi, Rahmat Alyakin; Nababan, Donal; Tarigan, Frida Lina (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Puskesmas Pematang Jaya as one of the Puskesmas located in Langkat Regency has a population of 15459 people. From the results of observations at the Pematang Jaya Community Health Center, the planning for the need for health personnel is still not perfect, so the policy in planning the need for personnel in one part of the Puskesmas is not sufficient. The number of tasks performed by a health worker affects the number and results of work that can be completed by each worker. The suitability of the number of employees with tasks in one of the activities can affect the productivity of the work unit which is carried out which results in unproductive work time and if there is a shortage of employees, excessive work will occur and affect the workload. This study aims to determine the amount of workload and how many health workers are needed in order to complete work programs at the Puskesmas effectively and efficiently. This research uses descriptive quantitative method. Research design by making direct observations of health workers and reviewing documents. calculating the energy requirements using the WISN method and then analyzed the results of the workload. The results showed that the need for personnel in the Puskesmas Pematang Jaya registration section according to the WISN calculation rounding instructions was 2.25, the Nursing section was 2.601 and the Puskesmas Laboratory section was 0.572. It is hoped that the results of this study can be a consideration to add personnel to the medical service division, such as doctors and nurses, and to add or replace parts that are not suitable for professional fields such as laboratory analysts, medical recorders and services that do not exist at all such as the nutrition department.